Reverse vascular pedicle digital island flap with preservation of the dorsal branch of the digital nerve. Issue 1 (1st January 2019) - Osaki, Takeo; Nomura, Tadashi; Hashikawa, Kazunobu; Terashi, Hiroto
Abstract: A reverse vascular pedicle digital island flap is a useful treatment option for reconstruction in fingertip amputation. We describe a surgical procedure to preserve the dorsal branch of the digital nerve in the middle phalanx during elevation of this flap with favourable outcomes.